Spanish refugees : memorandum of interview
026-0057-001 MEMORANDUM OF INTERVIEW. Date 23 June, 1939. Time to Reference EAB/AT/1053. Present SUBJECT. Spanish Refugees. Miss Pollock (Secretary, British Committee for Refugees from Spain. Telephone Sloane 9866), 'phoned to say she is going to Paris this weekend to discuss arrangements for emigration to Mexico and/or Chile of a number of Spanish refugees. They (the British Committee) have been offered 600 places in a passenger steamer and would like to know whether we want any of our people to be included. She wants to know this afternoon: (1) How many we will send from England. (2) Families (if any) in France to be picked up. (3) How much per head we are prepared to contribute towards the cost. (4) How balance (if any) is to be met. (5) Name of any other Committee likely to be interested. She referred to a financial offer you made this week at a Basque Committee meeting. Have 'phoned de Gondra at Basque delegation and he says about 200 of the 230 sailors in this country have expressed a desire to go to South America. He knows nothing of the arrangements referred to by Miss Pollock. I approached Mr. Tewson who said we would accept responsibility for 200 places, and would contribute between £8 and £10 per head towards emigration costs. I informed de Gondra at the Basque delegation who, after consulting Lizaso, expressed approval. Miss Pollock was then 'phoned, and she promised to keep us informed of developments. 292/946/26/57(ii)